Optimization System of Non-Medical Warehouse at UOBK Regional Hospital (A Quantitative Validation using WinQSB Software) - Nurilia Fitri Prabawati (Tech : Journal of Engineering Science, 2026)
The previous study at UOBK Regional Hospital provided many informative suggestions, but still did not achieve the main objective and didn’t show the quantitative validation. The previous study only showed the perspective by grouping the similar materials without any calculation for validation. However, this study provided a quantitative validation using the CRAFT algorithm with winQSB software in the form of a functional layout. Data was obtained from the previous study then it was calculated to be the input data for this study. By considering the field study and made some adjustment, it was acceptable using the previous study information not only to calculate the cost but also to calculate the layout coordinate. So this study integrated two previous studies to analyze how the outcome of layout recommendation from the previous study compared with its initial layout (raw data). The total material handling cost using winQSB calculated that the initial layout value was 25360.50. The optimum value of this initial layout was 25070.38. The results supported the layout recommendation on the previous study by adding admin desk and grouping the similar materials. This was demonstrated by the optimum value of layout recommendation, which was 19195.23 using the two-way exchange option. This study implied that the layout recommendation reduced until 77% of total material handling cost and demonstrated better value than its initial layout.